(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the importance of authentic materials in the development of listening comprehension skills in a foreign language. Majoring students should acquire skills that match their professional needs, for example, in the fields of engineering or medicine, through the use of materials that are close to real life. Authentic materials, including audio, video, and written materials, play an important role in preparing students to communicate in real-world situations. The results of the study indicate that such materials increase the motivation of students, help them to learn new lexical and grammatical structures. Authentic materials are also effective in strengthening students’ listening comprehension skills and introducing them to different accents and pronunciations. Future research highlights the importance of expanding strategies for the use of authentic materials and adapting them to different degrees. The article also shows the importance of authentic materials in making the educational process interesting and effective.